2006
DOI: 10.1097/01.brs.0000222020.45794.ac
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Flow Characteristics in the Cervical Epidural Space

Abstract: In cervical epidural steroid injections performed in the midline at C6-C7 and C7-T1, the contrast consistently covers the dorsal cervical epidural space bilaterally, irrespective of the volume used or neck flexion angle used. This suggests that solutions introduced here would cover the dorsal cervical epidural space. This questions the utility of performing potentially more dangerous injections at higher cervical levels or more invasive procedures, such as the use of epidural catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 4 publications
0
32
1
Order By: Relevance
“…7,31,89,90 Furthermore, to minimize the chance of a dural puncture, it is wise to perform ICESI at C7-T1 33 or at the highest, C6 -C7, as the epidural space is the largest in this area. 36 In addition, MRI should be obtained to ensure adequate space within the spinal canal of the level to be injected. If significant constriction is present at the level of pathology, ICESI should be performed at the level below or avoided completely.…”
Section: Discussionmentioning
confidence: 99%
“…7,31,89,90 Furthermore, to minimize the chance of a dural puncture, it is wise to perform ICESI at C7-T1 33 or at the highest, C6 -C7, as the epidural space is the largest in this area. 36 In addition, MRI should be obtained to ensure adequate space within the spinal canal of the level to be injected. If significant constriction is present at the level of pathology, ICESI should be performed at the level below or avoided completely.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 15 16 ] Yokoyama et al [12] showed that the contrast pattern is useful for predicting the distribution of local anesthetics. Other studies have shown that a 2 to 4 mL volume is adequate for contrast spread throughout the entire cervical epidural space, bilaterally.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that a 2 to 4 mL volume is adequate for contrast spread throughout the entire cervical epidural space, bilaterally. [ 15 16 ] In 1 study, a 5 mL volume was found to be optimal for distribution to the lower cervical spine in degenerative cervical spinal diseases [14] . However, these studies had some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, it has never been claimed that neck-flexion angle affects contrast spread. 23 In one study, it was suggested that an anterior shift of the posterior aspect of the dura during neck flexion probably results in a transient negative pressure in the posterior spinal canal, and consequently increases venous volume within the posterior epidural venous plexus, 24 which we believe could increase CEP.…”
Section: Discussionmentioning
confidence: 99%